2006
DOI: 10.1002/eji.200636294
|View full text |Cite
|
Sign up to set email alerts
|

NF‐κB binds to the immunoglobulin Sγ3 region in vivo during class switch recombination

Abstract: Ig class switch recombination (CSR) is dependent upon the expression of activation-induced deaminase and targeted to specific isotypes by germ-line transcript expression and isotype-specific factors. NF-κB plays critical roles in multiple aspects of B cell biology and has been implicated in the mechanism of CSR by in vitro binding assays and altered S/S junctions derived from NF-κB p50-deficient mice. However, the pleiotropic contributions of NF-κB to gene expression in B cells has made discerning a direct rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…It is noteworthy that p50 Ϫ/Ϫ cells are deficient in normal GT and in CSR (46), suggesting that the shift in Pax5 binding away from hs4 and back again are requirements for normal GT and CSR. It is of interest that the NFB and Pax5 binding sites are located 20 bp apart in hs4 (25), raising the possibility that engagement of one of these factors might affect occupancy of the other.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that p50 Ϫ/Ϫ cells are deficient in normal GT and in CSR (46), suggesting that the shift in Pax5 binding away from hs4 and back again are requirements for normal GT and CSR. It is of interest that the NFB and Pax5 binding sites are located 20 bp apart in hs4 (25), raising the possibility that engagement of one of these factors might affect occupancy of the other.…”
Section: Discussionmentioning
confidence: 99%
“…However, selection partially corrected the defect in exonucleolytic processing, resulting in a lesser abnormality in the productive repertoire. It is well-established that NF-B regulates different aspects of B cell apoptosis (2,9,12), proliferation (10,11,48), maturation (6, 9, 13, 49 -51), survival (8,49,52), class switch and Ig gene recombination (11,14,23,35,(53)(54)(55)(56)(57). In vitro studies examining Ikk␥ Ϫ/Ϫ embryonic stem cells cocultured with bone marrow cells (52) and in vivo studies using Mb-1Cre-transgenic mice lacking Ikk␥ from the B cell progenitor stage on (48) Previous studies have shown that NF-B signaling is defective in B cells of HED-ID patients (50).…”
Section: Discussionmentioning
confidence: 99%
“…NF-B p50 is critical for the germ line C H ␥3 transcription in response to stimulation and likely mediates chromatin remodeling at the S␥3 and S␥1 region through direct binding (72,82). Administration of the T-dependent nitrophenol-conjugated keyhole limpet hemocyanin immunogen to p50 Ϫ/Ϫ mice leads to smaller and decreased numbers of germinal centers (59,60).…”
Section: /P50mentioning
confidence: 99%